Eco-Friendly Anticorrosion Superhydrophobic Al2O3@PDMS Coating With Salt Deliquescence Self-Coalescence Behaviors Under High Atmospheric Humidity - Zhang, Binbin; Yan, Jiayang; Xu, Weichen; Yu, Teng; Chen, Zhuoyuan; Duan, Jizhou (Frontiers in Materials, 2022)
Bioinspired superhydrophobic coating was considered as a promising candidate for anti-corrosion applications due to the non-wetting physical barrier between metallic surface and the surrounding environments. However, it remains great challenges to develop robust superhydrophobic coating through facile one-step fluorine-free procedures to meet different functional requirements. Herein, we design and fabricate eco-friendly superhydrophobic Al2O3@PDMS composite coating with mechanical robustness based on hydrophilic Al2O3 NPs, intrinsically hydrophobic PDMS and versatile spray-coating approach. FE-SEM, EDS, XPS, Contact angle meter, electrochemical impendence spectroscopy and potentiodynamic polarization were utilized to characterize the surface micro-nano hierarchical morphologies, chemical compositions, surface wettability variations and corrosion resisting properties respectively. The |Z|0.01 Hz value of the superhydrophobic Al2O3@PDMS coating is 4 orders of magnitude higher than the bare Q235 carbon steel, indicating a superior corrosion resistance. The Ecorr of the as-fabricated superhydrophobic Al2O3@PDMS coating is considerably shifted to the positive direction by 0.27 V and the Icorr decreased by more than 4 orders of magnitude with a corrosion inhibition efficiency (η) of 99.992%. Besides, the single and double NaCl salt deliquesce behaviors with self-coalescence phenomenon of saline droplets were recorded to demonstrate Cassie-Baxter interfacial interaction of the superhydrophobic surface can serve as an efficient barrier to suppress the formation of saline liquid thin film and protect the underlying substrate from being corroded under atmospheric service environments with high relative humidity. It is believed that this robust superhydrophobic Al2O3@PDMS coating will provide a suitable large-scale technique to be easily applied to various substrates and find outstanding potential applications for liquids-repellency, self-cleaning, corrosion resistance, etc.